Astronomical calibration of the geological timescale: closing the middle Eocene gap - T. Westerhold; U. Röhl; T. Frederichs; S. M. Bohaty; J. C. Zachos (Climate of the Past, 2015)
To explore cause and consequences of past climate change, very accurate age models such as those provided by the astronomical timescale (ATS) are needed. Beyond 40 million years the accuracy of the ATS critically depends on the correctness of orbital models and radioisotopic dating techniques. Discrepancies in the age dating of sedimentary successions and the lack of suitable records spanning the middle Eocene have prevented development of a continuous astronomically calibrated geological timescale for the entire Cenozoic Era. We now solve this problem by constructing an independent astrochronological stratigraphy based on Earth's stable 405 kyr eccentricity cycle between 41 and 48 million years ago (Ma) with new data from deep-sea sedimentary sequences in the South Atlantic Ocean. This new link completes the Paleogene astronomical timescale and confirms the intercalibration of radioisotopic and astronomical dating methods back through the Paleocene–Eocene Thermal Maximum (PETM, 55.930 Ma) and the Cretaceous–Paleogene boundary (66.022 Ma). Coupling of the Paleogene 405 kyr cyclostratigraphic frameworks across the middle Eocene further paves the way for extending the ATS into the Mesozoic.